Towards identifying features of trust in mobile ad hoc network - Normalia Samian, 1979-, author; Mohd. Aizaini Maarof, author; Shukor Abdul Razak, author; Asia Modelling Symposium (2008 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL